The Challenges Facing Black Publishers in the '90s. - Adero, Malaika (Defining Ourselves: Black Writers in the 90s, 1999)
The article encourages African American writers to learn more about the business and the economics of publishing. Also, the author calls for black publishers to expand their visions internationally and to support other black artists in publishing ventures. There is a need for African Americans to understand various issues confronting their works in the publishing industry. These issues include the relationship of African American writers and readers to the mainstream publishing industry, the relationship between African American publishers and the industry, the relationship of African American publishers to their core markets, the relationship of the readership at large and the media and the relationship of African American authors and writers to independent Afro American publishers, etc.